Emancipating care - Barros, Nelson (Saúde e Sociedade, 2021)
The humanization of care has been a present challenge in the field of health in general and in the Brazilian Unified Health System. The purpose of this article is to discuss the sociological construct of emancipating care. While care is strongly identified with common sense and tacit knowledge, biomedical clinical practice has been associated with scientific knowledge resulting from a rationalist epistemological rupture. Emancipatory care is a hybridization between common sense and scientific knowledge, or care and clinic, supported by the professional’s ethical-political position, to replace heteronomy with autonomy in the health-disease-care process. The purpose of this article is to present an innovative perspective on the discussion of care, which is not new, bringing some historical references, not with the purpose of developing an epochalist or chronological analysis. The objective is to expand the space for reflections on heteronomous care as a hegemonic event in contemporary culture, as well as to expand the debates on the possibilities of building care practices that privilege people’s autonomy and point to their emancipation. It is concluded that the concept of emancipating care can advance a second epistemological rupture with the development of emancipating practices in the health-disease-care process.